Dilated Cardiomyopathy Concomitant with Acute Rheumatic Fever and Sporadic Hereditary Spherocytosis - Fitrisia Amelin; Didik Hariyanto; Amizah Zatil Izzah (Health and Medical Journal, 2020)
Background: Dilated cardiomyopathy (DCM) is a heart muscle disorder defined by the presence of a dilated and poorly functioning left ventricle in the absence of abnormal loading conditions (hypertension, valve disease) or ischaemic heart disease sufficient to cause global systolic impairment. Case report: A 5 years old and 6 months old girl with unremarkable cardiac history hospitalized for congestive heart failure due to dilated cardiomyopathy concomitant with acute rheumatic fever and sporadic hereditary spherocytosis. Acute rheumatic fever diagnosed based on the presentation of carditis, fever, high erythrocyte sedimentation rate, C-Reactive Protein (+), and antistreptolysin titer O (+). DCM was diagnosed after echocardiography. Sporadic hereditary spherocytosis was diagnosed based on anamnesis of pale and jaundice, splenomegaly on physical examination, hemolytic anemia, reticulocytosis, spherosit (+). Both parents reveals normal hematologic finding and the osmotic resistance test showed increasing of osmotic fragility. Conclusion: Prognosis of this patient remains worse because of inadequate left ventricle-right ventricle (LV-RV) function and highly increasing The N-terminal prohormone of brain natriuretic peptide (NT-proBNP) level.